Food Colorant as Corrosion Inhibitors for Aluminium-Copper Alloy in Trichloroacetic Acid - Pandya, J.M.; Joshi, S.D.; Hathi, M.V.; Acharya, G.D. (Asian Journal of Chemistry, 2010)
The inhibition of corrosion of aluminium-copper alloy (AI-Cu alloy) in trichloroacetic acid (TCA) is not much available. Therefore is this work the role of some food colourant in inhibiting the corrosion of AI-Cu alloy in solution of TCA has been reported. In order to determine the effect of inhibitor concentration on inhibitive efficiency weight losses were determined in 0.1 M TCA. At an inhibitor concentration 0.5% (w/v) the inhibitor efficiencies of various food colourants increased in the order: Fast red < Tatrazine < Carmosine < Sunset yellow < Amaranth The inhibition increases with increase in food colourant concentraton.